2020
DOI: 10.1017/s0959270920000349
|View full text |Cite
|
Sign up to set email alerts
|

Expert knowledge assessment of threats and conservation strategies for breeding Hen Harrier and Short-eared Owl across Europe

Abstract: Summary Hen Harrier Circus cyaneus and Short-eared Owl Asio flammeus are open-country birds of prey with overlapping distributions. Although both species face similar conservation threats across their ranges, work to date has largely been undertaken at a national scale with few attempts to collate and assess factors relevant to their conservation at an international scale. Here we use an expert knowledge approach to evaluate the impact of conservation threats and the effectiveness of conservation strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…The concept of carrying capacity encapsulates the notion that habitat resources must ultimately limit the numbers of raptors in an area. Nevertheless, factors other than those purely related to habitat characteristics (e.g., human pressure, intra-and interspecific interactions, period of the annual cycle) are known to affect local abundance and population dynamics [44,45]. Although our findings showed that species abundance and habitat suitability are significantly correlated, they also indicated that changes in abundance between 1997 and 2017 are not exclusively determined by changes in habitat suitability.…”
Section: Discussioncontrasting
confidence: 65%
“…The concept of carrying capacity encapsulates the notion that habitat resources must ultimately limit the numbers of raptors in an area. Nevertheless, factors other than those purely related to habitat characteristics (e.g., human pressure, intra-and interspecific interactions, period of the annual cycle) are known to affect local abundance and population dynamics [44,45]. Although our findings showed that species abundance and habitat suitability are significantly correlated, they also indicated that changes in abundance between 1997 and 2017 are not exclusively determined by changes in habitat suitability.…”
Section: Discussioncontrasting
confidence: 65%
“…Within Central Europe, both natural (e.g., bogs, coastal dunes, and marshes) and manmade habitats (e.g., agricultural land) are used for breeding (Keller et al 2020). Habitat loss and degradation, increased predation and reduced prey availability are considered to be the main threats of the Short-eared Owl in this part of its range (Fernández-Bellon et al 2020).…”
Section: Study Speciesmentioning
confidence: 99%
“…As a result, it is considered a species of conservation concern in Europe (Calladine et al 2012;Fernandez-Bellon et al 2020) and threatened with extinction in Germany (Ryslavy et al 2020). The owl has especially suffered from habitat loss and degradation due to agricultural intensification, increased predation and reduced prey availability (Fernández-Bellon et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In avian populations, negative responses to the changing climate have been documented globally (e.g. Both et al, 2006;Stephens et al, 2016), and in birds of prey, climate change has been proposed to influence many long-term population declines that have occurred in the past decades (Catry et al, 2011;Fernández-Bellon et al, 2020;Schmidt et al, 2012;Steenhof & Peterson, 2009). As birds of prey generally possess long life history cycles while their prey species with short generation times are capable of rapid responses to environmental shifts, they are particularly susceptible to drastic ecological changes (Meserve et al, 2003;Newton, 1979;Sergio et al, 2008).…”
Section: Introductionmentioning
confidence: 99%